2017
DOI: 10.1016/j.mce.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Cell signaling pathways in the adrenal cortex: Links to stem/progenitor biology and neoplasia

Abstract: The adrenal cortex is a dynamic tissue responsible for the synthesis of steroid hormones, including mineralocorticoids, glucocorticoids, and androgens in humans. Advances have been made in understanding the role of adrenocortical stem/progenitor cell populations in cortex homeostasis and self-renewal. Recently, large molecular profiling studies of adrenocortical carcinoma (ACC) have given insights into proteins and signaling pathways involved in normal tissue homeostasis that become dysregulated in cancer. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 148 publications
(223 reference statements)
2
12
0
Order By: Relevance
“…Shh is a member of hedgehog signaling pathway with well known mitogenic and morphogenic function during embryonic development [ Ingham et al, 2011 , Laufer et al, 2012 ]. Recent studies demonstrate implication of Shh signaling in regulation of adult stem cells involved in physiological regeneration of adult tissues [ Shin et al, 2011 , Peng et al, 2013 , Petrova and Joyner, 2014 , Penni et al, 2017 , Das et al, 2020 ]. Low proliferation rate in adrenal cortex of Shh mutants supports the idea that Shh is implicated in regulation of adult tissue homeostasis [ Ching and Vilain, 2009 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shh is a member of hedgehog signaling pathway with well known mitogenic and morphogenic function during embryonic development [ Ingham et al, 2011 , Laufer et al, 2012 ]. Recent studies demonstrate implication of Shh signaling in regulation of adult stem cells involved in physiological regeneration of adult tissues [ Shin et al, 2011 , Peng et al, 2013 , Petrova and Joyner, 2014 , Penni et al, 2017 , Das et al, 2020 ]. Low proliferation rate in adrenal cortex of Shh mutants supports the idea that Shh is implicated in regulation of adult tissue homeostasis [ Ching and Vilain, 2009 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Shh signaling pathway plays crucial roles in embryonic patterning and adult tissue homeostasis[13,14]. It was reported that the Shh signaling pathway was activated aberrantly in tumorigenesis and development of gastrointestinal, pancreatic, breast, lung, ovarian cancers and so on[15-18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the progenitor niche composition and cell identity, as well as the molecular mechanisms and paracrine factors involved in controlling the organ homeostasis, are still far from being completely understood. Indeed, any alteration in these processes at different developmental stages may underlie the functional hormonal defects and tumor development later occurring in the adrenal organ history (15,16). The current knowledge about the development and neonatal remodeling of the adrenal gland is limited, and nearly all models has been developed in animals (15), with only very scarce functional data available from studies of human fetal adrenals (17,18).…”
mentioning
confidence: 99%